L.A. Chic : a Locational History of Los Angeles Fashion. - Ingram, Susan (Urban chic., 2019)
Los Angeles is undergoing a makeover. Leaving behind its image as all freeways and suburbs, sunshine and noir, it is reinventing itself as walkable, ecologically healthy, and fashionable. This locational history of Los Angeles fashion and style allows us to understand the urban processes, desires and politics of re-imagining LA as the global, multi-ethnic city of the 21st century.